2017
DOI: 10.3390/su9050775
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Industrial-Suburban Heat Environment in a Mediterranean Area

Abstract: Abstract:The Urban Heat Island (UHI) phenomenon prevalently concerns industrialized countries. It consists of a significant increase in temperatures, especially in industrialized and urbanized areas, in particular, during extreme warm periods like summer. This paper explores the climate variability of temperatures in two stations located in Matera city (Southern Italy), evaluating the increase in temperatures from 1988 to 2015. Moreover, the Corine Land Covers (1990Covers ( -2000Covers ( -2006Covers ( -2012 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In particular, the fifth Assessment Report of the Intergovernmental Panel on Climate Change ascribed the dominant cause of the recent warming to human influence [6,7]. The overall effect of human activities on climate since the start of the industrial era has had a warming influence [8] especially in urban areas, leading to the Urban Heat Island (UHI) phenomena [9][10][11]. However, warming is variable in different seasons or in different locations.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the fifth Assessment Report of the Intergovernmental Panel on Climate Change ascribed the dominant cause of the recent warming to human influence [6,7]. The overall effect of human activities on climate since the start of the industrial era has had a warming influence [8] especially in urban areas, leading to the Urban Heat Island (UHI) phenomena [9][10][11]. However, warming is variable in different seasons or in different locations.…”
Section: Introductionmentioning
confidence: 99%
“…The urban heat island (UHI) effect is a most crucial issue, as its generation and evolution are closely related to social and economic activities. Studies on the distribution of UHI and its evolutionary mechanism have become a hot topic in multi-disciplines [3][4][5]. Furthermore, UHI also leads to an urban rain island effect, which concentrates heavy rain during the flood season and causes regional water logging in megacities such as Shanghai [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Urban Heat Island (UHI) effect has become more serious with the growth of urban areas and global climate change [1,2]. Studies have shown that the spatial extent and population of urban areas are increasing globally, and that the growth is expected to continue beyond the year 2100 [3,4].…”
Section: Introductionmentioning
confidence: 99%